Partnership in Cancer Research (PCAR) Program Increases Medical Student Knowledge and Confidence to Perform Cancer Research - Luis P. Marin; Jessica H. Presley; Katerina Noori; Diane McKinstry; Brandi Dawson; Kevin Sexton; Eric Peterson; Sarah Elizabeth Harrington; Jerad M. Gardner; Bolni Marius Nagalo; Behjatolah Montzavi-Karbassi; Steven R. Post; et al. (Journal of Cancer Education, 2024)
Arkansas has a high cancer burden, and a pressing need exists for more medical students to pursue oncology as a career. The Partnership in Cancer Research (PCAR) program provides a summer research experience at the University of Arkansas for Medical Sciences for 12 medical students who have completed their first year of medical training. A majority of participants spend time pursuing cancer research in basic science, clinical, or community-based research. Students report on their research progress in an interactive “Live from the Lab!” series and assemble a final poster presentation describing their findings. Other activities include participation in a moderated, cancer-patient support group online, lecture series on cancer topics, medical simulations, palliative care clinic visit, “Death Over Dinner” event, and an entrepreneurship competition. Students completed surveys over PCAR’s first 2 years in operation to evaluate all aspects of the program. Surveys reveal that students enthusiastically embraced the program in its entirety. This was especially true of the medical simulations which received the highest evaluations. Most significantly, surveys revealed that the program increased cancer knowledge and participant confidence to perform cancer research.